Pengembangan Perangkat Pembelajaran Berbasis Model PBL untuk Siswa Kelas V SD di Kabupaten Rembang - Febry Puspita Diningtyas; Fine Reffiane; Ryky Mandar Sary (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to develop learning tools based on the PBL model on the sub-theme of ecosystem components for grade V elementary school students who meet the quality criteria: valid, practical and effective. This type of research is research and development using the ADDIE model which consists Abstract The purpose of this study was to develop learning tools based on the PBL model on the sub-theme of ecosystem components for grade V elementary school students who meet the quality criteria: valid, practical and effective. This type of research is research and development using the ADDIE model which consists of 5 stages, namely the analysis, design, development, implementation and evaluation stages. The data analysis techniques used in this study are quantitative and qualitative descriptions. The results showed that each product met the criteria of validity, practicality, and effectiveness. The product meets the valid criteria indicated by the percentage of the material and media expert validation test, the learning tools (syllabus and lesson plans) reach a percentage of 90.51% and the teaching material module reaches a percentage of 91.05%. The product obtained the criteria of practicality indicated by the percentage of teacher responses to learning tools (syllabus and lesson plans) reaching 89.52% and teaching material modules reaching 88% and the percentage of student responses of 86.06%. The product meets the effectiveness criteria based on the learning outcomes of students on the competence of attitudes, knowledge and skills. The percentage of students who reached the KKM for knowledge competencies exceeded the average of 83.78 with the “high” classification. In conclusion, the PBL model based learning tools are feasible to use.